2015
DOI: 10.1111/jgs.13627
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Renin‐Angiotensin System May Slow Conversion from Mild Cognitive Impairment to Alzheimer's Disease

Abstract: Antihypertensives that modulate the renin-angiotensin system (RAS) on AD conversion in those with MCI has not been explored. Evidence suggests that blood-brain-barrier (BBB) permeability is necessary for these effects. We assessed the impact of RAS modulation on conversion to AD and cognitive decline in those with MCI, and the impact of BBB permeability and race on these associations. We analyzed data from the National Alzheimer’s Coordinating Center from the NIA-funded Alzheimer’s Disease Centers. We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 33 publications
2
67
0
1
Order By: Relevance
“…Overall, our results support findings from other studies associating midlife arterial hypertension with decreased late-life cognitive performance [36], while mildly higher BP in older people is inversely related to risk of dementia [1]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our results support findings from other studies associating midlife arterial hypertension with decreased late-life cognitive performance [36], while mildly higher BP in older people is inversely related to risk of dementia [1]. …”
Section: Discussionsupporting
confidence: 91%
“…In patients with mild cognitive impairment, diuretic use seems to have a differential benefit of reduced AD risk [35]. Nevertheless, most studies have shown conflicting results regarding the effects of distinct classes of antihypertensives on the incidence or course of AD [1], possibly due to specific characteristics of the populations studied - recently, one study reported more benefits from renin-angiotensin system modulation for African Americans than for Caucasians [36]. Anyhow, no class of BP-lowering medication caused significant differences in variations of BP or any test scores in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it should be emphasized that the centrally active ACE-Is (in contrast, noncentrally active ones) can impact cognitive functions (e.g., reduce risk for cognitive decline or dementia) via a possible anti-inflammatory or cerebral RAS-related actions and not by a blood pressure-lowering. [3738] Unquestionably, long-term prospective RCTs of centrally-active ACE-Is versus a noncentrally active ACE-Is would be warranted to establish further recommendations for centrally active ACE-Is as possible additional options to be adopted in the therapy of early AD stages or MCI. However, such evidence is not available yet and in the meantime, possible practical implications for many older patients at risk for dementia who have medical indications for the ACE-Is use (due to comorbidities, such as arterial hypertension, congestive heart failure, status post myocardial infarction, diabetes mellitus, or chronic kidney disease) might include a preferred choice of a centrally active ACE-I (e.g., captopril, fosinopril, lisinopril, perindopril, ramipril, or trandolapril) rather than a noncentrally active one.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, this includes trials using neuroimaging, and cerebrospinal fluid analysis, since they could elucidate the relation between AD and RAS, especially among patients in early AD stages. [37] Further clinical studies in patient groups with or without hypertension, and with elevated risk of AD (due to genetic predispositions, early onset of cognitive impairment, cardiovascular comorbidities, or ethnicity) should be conducted to explore whether the RAS-modifying medications, including centrally acting ACE-Is, should be considered for repurposing for AD indications in high-risk for dementia older patient populations. [37] It should be highlighted that outside of the large-scale clinical trials, there are only limited reports on the effects of centrally active ACE-Is on the rate of cognitive decline in elderly patients with dementia or its risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Demir, Gürol, Özyiğit, and Üresin (2016) performed a cross-sectional study and did not find a difference in the Mini Mental State Examination scores between renin angiotensin system (RAS) blocker users (angiotensin 1 receptors blockers [ARBs] and ACE-Is) and other AHM users. RAS blockers, which cross the blood-brain barrier, provide more cognitive benefit than those that do not cross the blood-brain barrier (Wharton et al, 2015). However, ARBs could be more effective than ACE-Is in improving cognition among patients with MCI (Hajjar et al, 2013).…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%